Weekly Vitamin D3 supplementation improves aerobic performance in combat sport athletes - Marley, A.; Grant, M. C.; Babraj, J. (European Journal of Sport Science, 2021)
Vitamin D3 supplementation can affect the strength and power of an athlete, however the effect on endurance performance remains unclear. Twenty-seven recreational male combat athletes with at least 12 months experience within combat sports were recruited (age: 24 ± 4 years, stature: 176 ± 6 cm, weight: 77 ± 14 kg). Participants completed baseline testing for blood haemoglobin and haematocrit, upper and lower body VO2peak and upper and lower body Wingate. Following testing participants were stratified to 50,000IU (D1), 80,000IU (D2) or 110,000IU (D3) of vitamin D3 per week. They then completed a 6-week placebo period followed by a 6-week supplementation period. Retesting was carried out after the placebo and supplementation period. There was a significant effect for time for haemoglobin and haematocrit, upper and lower body VO2peak and upper body Wingate power (P<0.01) but no effect for dose of vitamin D given. Performance data were normalised to vitamin D intake and there was a moderate effect size between D1 and D2 for lower body VO2peak (d=0.6), upper body VO2peak (d=0.13) and upper body average power (d=0.75), with a large effect size between D1 and D2 for haemoglobin (d=1.19), haematocrit (d=0.93) and upper body peak power (d=0.95). There was a large effect size for D1 compared to D3 for all variables (d>0.8). Therefore, there is no additional benefit to increasing dose above 50,000IU vitamin D per week. Given the endurance adaptations from vitamin D supplementation and the importance of endurance for combat performance, recreational combat athletes should supplement at 50,000IU per week for six weeks.